R44_Pygargue_Lorraine_LOANA_2021 ... - Inventaire National Du Patrimoine Naturel (UMS PatriNat (OFB-CNRS-MNHN), Paris, 2023)
Suivi de reproduction du Pygargue à queue blanche en Lorraine en 2021 par Loana ...